The role of Sharia Supervisory Board in the Sharia compliance process in Indonesia / Isni Andriana - Isni , Andriana (2018)
The Islamic banking industry has growth remarkable over the past few years. Nowadays, Islamic banks operate in nearly all-Muslim countries and many non-Muslim countries. The most important aspect in an Islamic bank is the Sharia compliance process. The Sharia Supervisory Board (SSB) is established to ensure an Islamic bank complies with the Sharia requirements. SSB as an independent board certifies and becomes an internal part of the Sharia governance framework in an Islamic bank to assure that all products, transactions, and operations in the bank comply with the requirements of Sharia. Sharia compliance process is one of the important tools in the Sharia governance framework within an Islamic bank. Several authors suggest that Sharia compliance process gives a crucial impact for an Islamic bank’s operation and business. The presence of the SSB as one of the Board of Directors (BoDs) committee in an Islamic bank differentiates the governance structure of an Islamic bank from a conventional bank. In this context, the issues on the roles of SSB in the Sharia compliance process are critical, since Sharia compliance is the bedrock and identity of an Islamic bank. The purpose of this study is to provide an in-depth understanding on the roles of SSB in assuring compliance with the Sharia requirements via the Sharia compliance process. Specifically, this study focuses on the role of the SSB as an independent body in an Islamic bank in facilitating the Sharia compliance process. The behavioural theory of board and professionalism are utilised to develop themes in understanding the role of the SSB in the Sharia compliance process. There are three dimensions from the behavioural theory of board that explain the ability of the SSB to perform it roles in the Sharia compliance process, known as effort norms, cognitive conflict, and the use of skills and knowledge. The theory of professionalism explains about the roles of the SSB contributes from the perspective of the professional power and the sustaining ideology. This study is conducted using a qualitative method adopting semi-structured interviews with open-ended questions. This study extends the existing literature by providing empirical evidence on the sharia compliance process as one of the important governance mechanism within an Islamic banking industry in Indonesia. Due to the limited empirical research in the field of Islamic accounting, especially in Indonesia, this study contributes towards filling this gap. This study presents two perspectives to develop the concept for evaluating the roles of the SSB in the Sharia compliance process in an Islamic bank. One, the findings point that; the roles of the SSB from the professionalism perspective are to advice, to regulate, to supervise and to audit. The Quran and Sunnah become the SSB’s sustaining ideology to perform their roles in ensuring Sharia compliance in Indonesian Islamic banks. Two, from the perspective of the behavioural theory of board this study reveals that the roles of the SSB are to regulate, to control, to monitor and to provide the required services to facilitate the Sharia compliance process. It is hopes that the findings from this study can contribute towards enhancing the roles of the SSB in the Sharia compliance process in Indonesian Islamic banks. Among others, in improving the process of nurturing the sharia talents, in developing the operational standards and ethical standard for the SSB, and in improving the level of independence among members of the SSB.